Effects of postnatal administration of ethanol on the M. gastrocnemius of the albino mouse - González-Hernández, T.H.; Molina-Rodríguez, A.; Llabrés-Olmo, J.; González-Reimers, C.E.; Pérez-González, H.; Meyer, G. (Drug and alcohol dependence, 1989)
A combined morphometric-histochemical (mATPase) study of the effects of ethanol during postnatal development on the m. gastrocnemius has been performed in the albino mouse. The experimental group received ethanol in the drinking water until sacrifice at the age of 40 days. Based on the fiber composition, three different areas are distinguished in the m. gastrocnemius of the mouse. The typical location of these areas does not change after ethanol administration. However, postnatal administration of ethanol produces a selective atrophy and a decrease of the number of type IIb (fast glycolytic) fibers. Concurrently, the number of type IIa (fast oxidative-glycolytic) fibers increases.